Refuge use by the coconut mite Aceria guerreronis: fine scale distribution and association with other mites under the perianth - Lawson-Balagbo, L.M.; Gondim, M.G.C.; Moraes, G.J. de; Hanna, R.; Schausberger, P. (Elsevier, 2007)
The tiny size of eriophyoid mites is a key feature regarding their status as herbivorous pests. Many eriophyoid species are highly host specific and live in concealed sites (refuges) on their hosts, which are difficult to access by natural enemies. We explored the spatial refuge used by one of the most important coconut pests, the coconut mite Aceria guerreronis Keifer (Eriophyidae). Based on the assumption that A. guerreronis shifted its habitat under the perianth of coconut to avoid competition and/or escape from predation we investigated the fine scale spatial distribution of A. guerreronis and associated competitors and predators. Coconut fruits were sectioned and discrete chambers identified under the perianth. A. guerreronis was present on 92% of fruits and by far the most abundant mite under the perianth. It preferentially resided in the tightest chambers to the fruit surface. Another herbivore, Steneotarsonemus furcatus De Leon (Tarsonemidae) was found on ∼30% of fruits most of which were simultaneously occupied by A. guerreronis. Neoseiulus baraki Athias-Henriot (Phytoseiidae) was the predominant predatory mite (∼35% of fruits) followed by Proctolaelaps bickleyi Bram (Ascidae) (∼7% of fruits). A. guerreronis, S. furcatus and N. baraki showed a slightly different but more similar repartition among chambers under the perianth than P. bickleyi. Overall, our study suggests that refuge use by A. guerreronis is a key issue for its natural and/or biological control. Potential control strategies are discussed.